Bioinformatic analysis of the clinicopathological and prognostic significance of oocyte-arresting BTG4 mRNA expression in gynecological cancers - Hua-chuan Zheng; Hang Xue; Cong-yu Zhang; Rui Zhang (Taylor & Francis Group, 2023)
BTG4 arrests the cell cycle and suppresses oocyte and embryonic development. We performed a bioinformatic analysis of BTG4 expression. BTG4 expression was downregulated in breast cancer compared with normal tissues (p < .05), but the opposite was observed in cervical, endometrial and ovarian cancers (p < .05). BTG4 methylation was negatively correlated with its mRNA expression in breast, cervical and endometrial cancers (p < .05). BTG4 mRNA expression was negatively correlated with T staging and distant metastasis of breast cancer; and with tumor invasion, clinical stage, low weight and BMI, low histological grade and no diabetes in endometrial cancer but positively with T stage and non-keratinizing squamous carcinoma in endometrial cancer. BTG4 expression was negatively correlated with the survival of ovarian cancer patients (p < .05), but positively for breast, cervical and endometrial cancers (p < .05). BTG4 expression is thus a potential marker reflecting the carcinogenesis, aggressiveness and prognosis in gynecological cancers.Impact Statement What is already known on this subject? Previous studies have revealed the structure and location of BTG4. BTG4 inhibit cell proliferative, promote apoptosis, induce G1 cell cycle arrest. BTG4 promotes the development of mouse embryos from cell stage 1 to 2. The methylation and biological function of BTG4 were clarified in gastric and/or colorectal cancer cells. What do the results of this study add? BTG4 is found to closely link to reflect the carcinogenesis, histogenesis, aggressive behaviors and prognosis of gynecological cancers, and involved in ligand-receptor interaction, microtubule motor activity, dynein light chain binding, cilium organization, assembly, and movement in endometrial and ovarian cancers. What are the implications of these finding for clinical practice and/or further research? Aberrant BTG4 mRNA expression can be employed as a marker of the tumorigenesis, histogenesis, aggressiveness and prognosis of gynecological cancers in the future practice and guide the investigation of BTG4-related signal pathways.